Experimental assessment and numerical simulation of the large deformation of a flexible composite tank - Liu, Yuxi; Chen, Yu; Shan, Zhiyong; Li, Qian; Lin, Guochang (Frontiers in Materials, 2022)
A flexible composite tank is developed for storage of oil and gas. The tank is made of coated fabric, which is a thermoplastic polyurethane reinforced aramid fiber, to satisfy strength, sealing, and fluid compatibility requirements. The top and bottom areas of the tank are connected with a rod to fix the tank height during inflation. The tank deformation is studied. Experimental tests are conducted on two prototypes of 0.4 m height and a prototype of 1.7 m height in water basin. The test on small prototype focuses on obtaining deformed shapes. The test on 1.7 m height prototype focuses on obtaining strain sensor readings. The tank collapses initially from the bottom part, propagates upward, and then finally, only the top part retains the initial shape when the tank is empty. The deformation process is also simulated using finite element model. Results show that the deformation shape of the tank was simulated effectively compared with that in the experimental result. The finite element analysis (FEA) results are conservative compared with the test result given that the tank deformation is irregular and maximum strain is difficult to record during the test. This research provides insight on the deformation behavior of flexible tank, and the validated FEA model can be used for future optimize design.